2020
DOI: 10.21037/jgo-20-510
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of the TP53 R249S mutation in hepatocellular carcinoma with aflatoxin B1 exposure and infection with hepatitis B virus

Abstract: Background: Exposure to dietary aflatoxin B1 (AFB1) induces DNA damage and mutation in the TP53 gene at codon 249, known as the TP53 R249S mutation, and is a major risk factor for hepatocellular carcinoma (HCC). AFB1 and the hepatitis B virus (HBV) together exert synergistic effects that promote carcinogenesis and TP53 R249S mutation in HCC.Methods: A genome-wide association study (GWAS) of whole genome exons was conducted using 485 HCC patients with chronic HBV infection. This was followed by an independent r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Among more than 20 kinds of aflatoxin derivatives, AFB 1 possesses the highest toxicity of liver cancer and immune system damage. AFB 1 causes carcinogenesis in the presence of the double bond of AFB 1 furan ring by inhibiting RNA synthesis [ 4 ]. The lactone ring of AFB 1 is the main toxicity site.…”
Section: Introductionmentioning
confidence: 99%
“…Among more than 20 kinds of aflatoxin derivatives, AFB 1 possesses the highest toxicity of liver cancer and immune system damage. AFB 1 causes carcinogenesis in the presence of the double bond of AFB 1 furan ring by inhibiting RNA synthesis [ 4 ]. The lactone ring of AFB 1 is the main toxicity site.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it participates in a family of genes that encode proteins regulating various cellular functions, such as cell division and cell fate determination, ontology-enriched pathways, transcription, transmembrane signaling, mRNA modification, and vesicle fusion [ 27 , 28 ]. However, in a GWAS study of patients with hepatocellular carcinoma and chronic hepatitis B virus (HBV) infection, Han et al (2020) reported low expression of WDR49 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other less common causes of cirrhosis contribute to a risk of developing HCC, including primary biliary cirrhosis, autoimmune hepatitis and hemochromatosis [ 29 , 30 , 31 , 32 ]. In some regions of Asia and Africa, exposure to aflatoxin B1, due to fungal contamination of staple foods, is related to the development of mutations (TP 53 codon 249, known as TP53 R249S) that lead to the development of HCC in patients with HBV infection [ 21 , 22 , 28 , 33 ].…”
Section: Epidemiologymentioning
confidence: 99%